Strategi Peningkatan Daya Saing Sektor Jasa Pariwisata Indonesia: Studi Kasus Jasa Pariwisata Danau Toba dan Bali: Strategies for Increasing Competitiveness of Indonesia's Tourism Services Sector: Case Study of Lake Toba And Bali Tourism Services - Widyastutik; Iskandar Panjaitan; Florika Malau; Youshy Fahreiza (Jurnal Aplikasi Bisnis dan Manajemen (JABM), 2020)
The tourism sector contributed as the third largest foreign exchange in 2017 after coal and palm commodities that amounted to 14.86 billion US $. In another condition, tourism services export’s growth is lower than other sector. This research is aiming to (1) analyze tourism service performance, (2) Develop a strategy to increase the competitiveness of Indonesia's tourism sector with a case study of the tourism service sector in Lake Toba and Bali. Bali is chosen as a research location because it becomes a benchmark for the development of 10 destination priorities for Indonesia's tourism, while Lake Toba becomes one of the priorities for the development of increased tourist visits to Indonesia. This research uses primary and secondary data. Primary data are obtained from distributing questionnaires in in-depth interviews and FGDs. While secondary data come from the Central Statistics Agency, Bank of Indonesia, The World Economic Forum, and The World Bank. The analytical method used is Analytical Hierarchy Process (AHP). The results show that tourists visiting Indonesia are dominated by countries in the ASEAN and other Asia Pacific regions such as Malaysia, China, Singapore, Australia, Timor Leste, Japan, India, and South Korea. Furthermore, other partner countries included in the Top 15 are the United Kingdom, the United States, France, Germany, and the Netherlands. The priority strategy for increasing competitiveness of Indonesia’s tourism services case studies Toba Lake and Bali are government facilitation and synergy between Ministries/Institutions followed by a strategy to create a business climate with friendly regulations and finally a strategy to strengthen tourism support infrastructure. Keywords: competitiveness, services export’s, tourism service sector, AHP